2021
DOI: 10.1155/2021/6676092
|View full text |Cite
|
Sign up to set email alerts
|

Driver Lane-Changing Behavior Prediction Based on Deep Learning

Abstract: A correct lane-changing plays a crucial role in traffic safety. Predicting the lane-changing behavior of a driver can improve the driving safety significantly. In this paper, a hybrid neural network prediction model based on recurrent neural network (RNN) and fully connected neural network (FC) is proposed to predict lane-changing behavior accurately and improve the prospective time of prediction. The dynamic time window is proposed to extract the lane-changing features which include driver physiological data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Wu et al [35] proposed a joint IRL-DL framework to predict drivers' future behavior in ride-hailing platforms, achieving consistent and remarkable improvements over models without drivers' preference vectors. Wei et al [36] proposed a hybrid neural network prediction model based on RNN and a fully connected neural network (FC) to accurately predict lane-changing behavior in real traffic scenarios. The proposed model achieved a prediction accuracy of 93.5% and improved the prospective time of prediction by about 2.1s on average.…”
Section: Related Workmentioning
confidence: 99%
“…Wu et al [35] proposed a joint IRL-DL framework to predict drivers' future behavior in ride-hailing platforms, achieving consistent and remarkable improvements over models without drivers' preference vectors. Wei et al [36] proposed a hybrid neural network prediction model based on RNN and a fully connected neural network (FC) to accurately predict lane-changing behavior in real traffic scenarios. The proposed model achieved a prediction accuracy of 93.5% and improved the prospective time of prediction by about 2.1s on average.…”
Section: Related Workmentioning
confidence: 99%
“…Relevant scholars have carried out a large number of explorations using to construct driving behavior models and achieved good results. For example, Li et al [31] and Wei et al [93] used RNN to predict lane change behavior, and the accuracy reached 96% and 93.5%, respectively. EdDoughmi et al [32] identified fatigued driving behaviors by inputting the collected video stream data of drivers' faces into the 3D-RNN model established, with an accuracy of 92%.…”
Section: Recurrent Neuralmentioning
confidence: 99%
“…The prediction of the surrounding environment by the intelligent driving system has always been a difficulty in the industry, especially in the intelligence of the bicycle. Because the field of vision of the sensor is blocked by the surrounding vehicles and other things, its detection range is limited, so the vehicle can get less environmental information, and the difficulty of prediction is further increased [ 21 ].…”
Section: Introductionmentioning
confidence: 99%